A methodology of study of three dimensional stratified turbulent fluid flow for hydroelectric power plant reservoir simulation. - Shin, Hyun Ho (2009)
To study and forecast the environmental impacts that a hydroelectric power plant reservoir may produce, a numerical simulation that takes into account the effects of stratification and scalar mixing (such as temperature, salinity or water-soluble substance) is required. This work proposes a methodology for the study of the environmental fluid flow phenomena, mainly for flows in which the knowledge of the interaction between stratification and mixing can give important notions of the phenomena that occur. For this, a numerical simulation tool for 3D environmental flow is developed. A tetrahedral mesh generator of the reservoir based on the terrain topology and an algebraic turbulence model based on the Richardson number are the main tools developed. The main difficulty in tetrahedral mesh generation of a reservoir is nonuniform distribution of the points related to the huge ratio between the horizontal and vertical scales of the reservoir. In this type of point distributions, conventional tetrahedron mesh generation algorithm may become unstable. For this reason, a unstructured tetrahedral mesh generator is developed and the methodology used to obtain conforming elements is described. Triangular surface mesh generation using the Delaunay triangulation and the construction of the tetrahedra from the triangular surface mesh are the main steps to the mesh generator. The hydrodynamic simulation of reservoirs with a turbulence model provides a useful tool that is computationally viable for engineering purposes. Furthermore, the turbulence model based on the Richardson number takes into account the effects of interaction between turbulence and stratification. The algebraic model is the simplest among the various models of turbulence, but provides realistic results with the fitting of a small amount of parameters. Eddy-Viscosity/Diffusivity models for stratified turbulent flows models are incorporated. Using the Finite Element Method (FEM) approximation the Reynolds-averaged Navier-Stokes (RANS) and mean scalar transport equations are approximated. The convective terms are discretized employing the Semi-Lagrangian method, and the spatial discretization is based on the Galerkin method. The computational results are compared with the results available in the literature. Finally, the simulation of the flow in a branch of a reservoir is presented.